Cost-effectiveness of stress CTP versus CTA in detecting obstructive CAD or in-stent restenosis in stented patients - Kim, Seung Hyup; Rübenthaler, Johannes; Nörenberg, Dominik; Huber, Thomas; Kunz, Wolfgang Gerhard; Sommer, W. H.; Schönberg, Stefan; Janssen, Sonja; Overhoff, Daniel; Froelich, Matthias F. (European radiology, 2021)
The aim of this retrospective study was to determine cost-effectiveness of stress myocardial CT perfusion (CTP), coronary CT angiography (CTA), and the combination of both in suspected obstructive coronary artery disease (CAD) or in-stent restenosis (ISR) in patients with previous coronary stent implantation.